Are Family Allowances and Fertility-related pensions Siamese Twins? - Robert Fenge; Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper discusses alternative ways to deal with the positive externalities of having children in a pay-as-you-go pension system. Family allowances are compared to introducing a fertility-related component into the pension formula. In an endogenous labor supply setting, both instruments are shown to be equivalent if general pensions are of the Bismarckian contribution-related type. In contrast, if general pensions are of the Beveridgean flat-rate type, making pensions contingent on the number of children is generally preferable to family allowances because the latter creates a larger tax load on labor supply.
Keywords: H23; H55; J13; J18; 330; pay-as-you-go pension; child benefits; fertility; externalities